Let's Play - Murray, William; Stories by Jill Corby and Illustrated by Chris Russell (London Ladybird, 1993)
'Read With Me' adopts the look-say approach, introducing learners to the first 300 most frequently used words in the English language. Pronunciation and meaning are learned through gradual introduction and careful repitition.
Include Color Illustrations
Key Words Reading Scheme
Keywords: Play